Model Sinergi Koperasi Merah Putih dan UMKM dalam Meningkatkan Keberlanjutan Ekonomi Lokal di Indonesia - Alfisyahrin, M; Azwari, Peny Cahaya; Zahara, Anzu Elvia; Nuraliati, Ayke (Badan Penelitian dan Pengembangan Daerah KabupatenMuara Enim, 2025)
This study aims to develop an integrative model of synergy between the Koperasi Merah Putih and micro, small, and medium enterprises (MSMEs) in strengthening local economic sustainability in Indonesia. Using a quantitative explanatory approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM), the research examines the relationships among cooperative governance (X₁), digitalization (X₂), MSME performance (Y), and local economic sustainability (Z). Data were collected from 250 cooperative managers and MSME members. The findings demonstrate that transparent and accountable cooperative governance combined with digital transformation fosters MSME productivity, efficiency, and inclusivity—contributing to the resilience of local economies. This study provides theoretical implications for the institutional economics of cooperatives and practical policy recommendations to promote sustainable local development through cooperative MSME collaboration